Is sedentary behavior an intervening factor in the practice of physical activity in the elderly? - Oliveira,Daniel Vicentini de (2018)
Abstract Objective: the present study aimed to analyze the association between current sedentary behavior and the practice of physical activity among elderly persons in the city of Maringá in the state of Paraná. Method: a cross-sectional study of 970 elderly subjects was carried out, using the International Physical Activity Questionnaire. Results: the modeling of structural equations revealed that the sedentary behavior has a significant effect (p <0.05) on the activities moderate and vigorous activities, explaining 3% and 4% of the variability of these variables. Specifically, it has been found that increased sedentary behavior has a (β = 0.13) and negative on vigorous activities (β = -0.21). Conclusion: the current state of sedentary behavior has a significant effect on moderate and vigorous activities.